A Mechanistic and Quantitative Understanding of the Interactions between SiO and Graphite Particles. Issue 2 (27th November 2022) - Gao, Xiang; Li, Suli; Xue, Jiachen; Hu, Dianyang; Xu, Jun
Abstract: SiO, comprised of silicon and silicon dioxides (SiO2 ), is one of the most commercially promising anode materials to mix with current widely used graphite for the high energy density lithium‐ion batteries (LIBs). One of the major bottlenecks for SiO/Graphite (SiO/Gr) composite anode is the cyclability due to considerable stress and strain (deformation) caused within and among the composite particles. However, a sophisticated and quantitative understanding of the highly electrochemical–mechanical coupling behaviors is still lacking. Herein, an electro–chemo–mechanical model with a detailed geometric description to quantitatively reveal the underlying governing mechanisms of SiO/Gr composite anodes using the half‐cell configuration is established and validated. Results show that an 8–10 wt.% of SiO is an optimal choice regarding capacity delivery and minimizing Li plating under 1C constant current charging condition. Positioning SiO particles near the separator and reducing the sizes of SiO particles are also demonstrated to be beneficial for electrochemical performance with trivial influence on mechanical mismatch. This study highlights a promising multiphysics model for the design and evaluation of next‐generation batteries and unlocks the mechanistic and quantitative understanding of the interactions among composite particles in electrodes. Abstract : An electro–chemo–mechanical coupled model with a detailed geometric description is established to quantitatively reveal the underlying governing mechanisms of SiO/Graphite composite anodes using the half‐cell configuration. The effects of SiO weight percentages, SiO distributions, SiO sizes, and C‐rates on the battery performance are discussed. A powerful tool and significant anode design guidance are then provided according to the results.